PERSEPSI DAN HARAPAN MASA KINI DAN MASA DEPAN ANAK JALANAN - Muhammad Kurniawan; Rosmawati Rosmawati; Siska Mardes (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to know the characteristics of street children, the perception of street children to their work, the current and future hope of street children in the street of Harapan Raya, Pekanbaru city. The study used a qualitative and descriptive approach. The data source in this study was a street child of 6 people who took the Purposive Sampling technique. Data collected using instruments include observation and structured interviews. Results obtained psychological characteristics of street children is difficult to meet face to face and communicate directly, tend to be reckless, lability and want compassion. Physical characteristics of street children, among others, have a thin body, reddish black hair, brown skin mature and dull, and often use clothes that look dull. The street child sees his current work as an attempt to help the family economy. Their perception of work is derived from the closest people, namely, parents, brothers, sisters, and friends. During work on the streets the children get a pleasant and depressing experience. They have a hope of being able to quickly finish their work and quit their job as street children, and they have the ideals they want to achieve. Their parents know and support to realize their children's ideals. Learning is enterprising and school highest be their way and effort to reach the expected futureKey Words: Perception, Hope, the Street Children